Influence of Locus of Control on Internet Addiction among Kwara State Colleges of Education Students - Jamiu Babatunde Bello; Habibat Bolanle Abdulkareem; Abdulhafis Adeyinka Hassan; Ameenat Arinola Ogo-oluwa; Abdulkareem Olalekan Abubakar (Jurnal Pendidikan Multimedia (Edsence), 2023)
The study investigated the influence of locus of control on internet addiction among undergraduate students in Kwara State. A descriptive survey design with one research question guided the study. Two hypotheses were formulated and tested in the study. The population comprises all full-time undergraduate students at Kwara State College of Education, Ilorin. The samples consist of 500 full-time undergraduates. The researcher randomly selected 200 males and 300 females undergraduate students. Data were collected using the adopted locus of control scale and internet addiction scale to measure the level of internet addiction among undergraduate students at Kwara State College of Education. The collected data were analyzed using frequency, mean, percentage, standard deviation and t-test. It was revealed that there is a significant difference in the locus of control and internet addiction among Kwara State College of Education students. The result further shows that gender does not affect the internal and external locus of control of the male and female respondents. It was concluded that there is gender influence on the locus of control and internet addiction while there is no gender influence in the way both internal and external locus of control students are addicted to the internet. It was recommended that strategies and activities that would build students’ locus of control and reduce internet addiction be put in place to assist students generally.